Proposal for Reforming Prehospital Response to Chemical Terrorism Disasters in Japan: Going Back to the Basics of Saving the Lives of the Injured by Securing the Safety of the Rescue Team. Issue 1 (6th February 2020) - Anan, Hideaki; Otomo, Yasuhiro; Homma, Masato; Oshiro, Kenichi; Kondo, Hisayoshi; Shimamura, Fumihiko; Takahashi, Ayako; Hamada, Masahiko; Hirabayashi, Atushi; Koido, Yuichi
Abstract: Introduction: Having experienced the Tokyo subway sarin attack in 1995, Japan has established extremely strict rules on handling injured victims before they are sent to a hospital. As a result, it takes a long time before rescue actions are taken. This report aims to propose a reform to change the system that focuses on saving lives. Methods: First, the issues in firefighting on sites that currently present problems in Japan were identified. Then, Japanese guidelines were compared with those that were considered in other countries. Based on this, an ideal way of running rescue operations was examined, and a proposal to save many lives was made. This research was conducted with funding from the Ministry of Health, Labour, and Welfare of Japan (MHLW; Chiyoda, Tokyo, Japan). Results: In addition to preventing secondary injuries, the temporal aspect of rescuing people early with the clear goal of saving many lives was emphasized. Priority was given to measures against nerve agents to prevent secondary injuries, which put the rescuers' lives at risk. Possible decontamination methods were pursued before choosing the one that was most appropriate. A linear algorithm was used to determine which decontamination method could be started immediately, and then the gradual use of equipment was recommended. Even if Level A personal protective equipment (PPE) and other dedicated equipment and materials cannot be procured, the possibility of starting rescue activities under certain condition using regular equipment was pointed out. The need for a system for possible victims who would require support, such as foreigners, the handicapped, and elderly people, was also identified. Japan limits the scope of activities that can be undertaken by emergency medical technicians (EMTs) on-site. The way in which on-site medical care can be provided with future legal revisions in mind was also discussed. Conclusion: There is an urgent need to build a framework in which rescue activities can take place so that the number of deaths would not rise, even if sarin and other poisons are scattered.